How the “History of Advertising” was written: Historiographical basis and periodization scheme - Méndiz Noguero, Alfonso (Historia y Comunicación Social, 2014)
Nowadays books about history of advertising differ in structure and historical foundation. In this paper we study the first books published about the subject (between 1874 and 1968) to discover where the origins of advertising lies, what periodization scheme are used and which advertising concepts are assumed to consolidate first scientific basis in this field.